2008
DOI: 10.1161/circulationaha.107.711911
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Allograft Vasculopathy

Abstract: Abstract-Cardiac allograft vasculopathy (CAV) continues to limit the long-term success of cardiac transplantation.Recent insights have underscored the fact that innate and adaptive immune responses are involved in the pathogenesis of CAV. Vascular lesions are the result of cumulative endothelial injuries induced both by alloimmune responses and by nonspecific insults (including ischemia-reperfusion injury, viral infections, and metabolic disorders) in the context of impaired repair mechanisms. Intravascular ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
262
1
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 403 publications
(275 citation statements)
references
References 143 publications
(162 reference statements)
5
262
1
7
Order By: Relevance
“…[19][20][21][22] A variety of studies investigating coronary artery disease in heart transplant patients, who have baseline endothelial dysfunction, have shown that antiproliferatives such as sirolimus attenuate the rate of atherosclerotic progression. 29,30 In addition, paclitaxel is a well-known immunomodulatory agent and has also been associated with atherosclerotic regression in animal models, as well as reduced inflammation in stented porcine arteries. 23,31 Furthermore, given that the product labeling and pharmacokinetic studies in sirolimus-eluting stents describe serum detectability of antiproliferative agents for over 2.5 weeks and an estimated 3 month elution period after implantation (depending on stent type), one would expect these drugs to have long-term effects on the downstream vascular bed.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] A variety of studies investigating coronary artery disease in heart transplant patients, who have baseline endothelial dysfunction, have shown that antiproliferatives such as sirolimus attenuate the rate of atherosclerotic progression. 29,30 In addition, paclitaxel is a well-known immunomodulatory agent and has also been associated with atherosclerotic regression in animal models, as well as reduced inflammation in stented porcine arteries. 23,31 Furthermore, given that the product labeling and pharmacokinetic studies in sirolimus-eluting stents describe serum detectability of antiproliferative agents for over 2.5 weeks and an estimated 3 month elution period after implantation (depending on stent type), one would expect these drugs to have long-term effects on the downstream vascular bed.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of coronary angiography alone for CAV is suboptimal because of the diffuse nature of the disease and lack of a normal reference vessel for grading stenosis in many cases. 3,5,20 Despite the lack of sensitivity for early CAV lesions, angiography provides important prognostic information and reliably excludes obstructive CAV. 3 The International Society of Heart Lung Transplantation (ISHLT) has developed a nomenclature to help standardize the way CAV is reported and compared which has become the preferred classification system 1 ( Figure 4).…”
Section: Invasive Testingmentioning
confidence: 99%
“…18 Although not completely understood, it is thought that the pathogenesis of CAV involves repeated injuries to the endothelium from a variety of factors such as cellular-mediated rejection, alloimmune factors, ischemiareperfusion injury at time of transplant, CMV infection, immunosuppression medications, systemic inflammation, and traditional atherosclerosis risk factors. 3,[19][20][21] A schematic and theoretical progression of disease is illustrated below. Damage to the endothelium leads to smooth muscle cell proliferation, infiltration of the intima with inflammatory cells, and collagen deposition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CAV is characterized by intimal proliferation which progresses at different periods after transplantation, resulting in a luminal narrowing in the allograft arteries and is the leading cause of morbidity and mortality in cardiac transplant recipients 1 . Therefore, CAV represents a major clinical concern and the focus of research 2,3.…”
Section: Introductionmentioning
confidence: 99%